A geochemical assessment method for identification of natural pozzolans as supplementary cementitious material. Issue 12 (5th December 2021) - Pourkhorshidi, A. R.; Sobhani, J.; Ramezanianpour, A. A.
Abstract : Pozzolans are available in natural resources as raw materials that are potentially applicable in the cement and concrete industries. Proper identification and exploration methods are crucial in relation to their technical and economical purposes. In this paper, a two-phase study is employed, based on geochemical data processing and experimental investigations. Chemical and petrography of natural pozzolans were utilised to develop the proposed method. This method proposes three geochemical indexes: the limiting values of silica/calcium oxide (SiO2 /CaO), alumina saturation and alkali content to qualify the natural pozzolan according to the supplementary cementitious requirements. Then, based on ASTM C618 and EN 196-5 standards and complementary tests, the chemical and physical properties of two natural pozzolans were assessed to validate the proposed method. The results showed that this method could be used as a robust and direct way to identify natural pozzolans.